An interesting case of recurrent shortness of breath and pleuritic chest pain - Price, Kathryn (Breathe (Sheff), 2018)
Can you diagnose this case of a 58-year-old male with sudden-onset shortness of breath associated with sharp right-sided pleuritic chest pain? http://ow.ly/HLmk30j4DEH